Visualisasi Pencarian Lokasi Tempat Kuliner Dan Wisata Di Kota Siantar Menggunakan Collaborative Filtering - Roberto Nainggolan; Yunita Sari Siregar; Mufida Khairani (UIN Sumatera Utara, 2021)
Tourist and culinary places are a trip or visit to a place with the aim of trying or tasting local specialties to enjoy the food and drinks that exist in the area. There are many tourist and culinary places in Indonesia that can be visited by tourists, one of which is culinary tourism in the city of Siantar. Enjoying culinary is the main goal for tourists in choosing tourist and culinary places. Convenience is a factor that influences tourists when they want to visit tourist and culinary places and sometimes tourists find it difficult to determine which tourist and culinary places to visit with the variety of tourist and culinary attractions available. For this reason, information about tourist and culinary attractions in the city of Siantar is needed by tourists who are visiting the city. This application is designed based on a website and uses a collaborative filtering algorithm method that will provide recommendations in the form of address information, ratings that have been given by previous users, and provide recommendations based on visiting patterns by users who have visited these tourist and culinary places. Keywords: Culinary, Tourist attraction, Siantar City, Website, Collaborative Filtering